Biology and cast properties of soil-dwelling earthworm of Kaki Bukit, Perlis, Malaysia - Teng, Suk Kuan (2012)
Soil dwelling earthworms have close association with soil and plant root systems. They promote organic matter decomposition and nutrient cycling in soils. Present study was carried out to examine the physico-chemical parameters which may influence the diversity, density and biomass of earthworm community in Kaki Bukit,Perlis. The area is mainly planted with rubber and fruit trees and is surrounded by limestone hills, thus serves as an unique agroecosystem to be explored. Earthworms and soil samples were collected for identification and analyses in the laboratory. Both morphology and molecular techniques were adopted to identify earthworms up to species level. In molecular identification, the primers used are from COI (cytochromec oxidase I) and 16S rRNA genes. The area was found to be dominated by Metaphire tschiliensis schiliensis, a relatively large-sized soil dwelling earthworm that showed active surface casting activity. Its density has positive correlation with soil pH (r =0.645), clay content (r = 0.801), total N (r= 0.596) and total Ca (r = 0.415) whilst negatively correlated with Fe. In addition, earthworm biomass was found to be positively correlated with K concentration (r = 0.374). Present study demonstrated that surface casts produced by M. tschiliensis tschiliensis contained higher total carbon, humic acid, N, Ca, S and Zn contents compared to worm worked soil and bulk soil. Earthworm casts also have higher microbial (bacteria and fungi) populations than worm worked soil and bulk soil which in turns led to higher nutrient contents in arthworm casts. The study highlighted the beneficial effects of M. tschiliensis tschiliensis onto soil and to be potentially serves as soil bioconditioner in tropical agroecosystem.